2023
DOI: 10.3390/ijms24109041
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Fibroepithelial Lesions of the Breast

Abstract: Fibroepithelial lesions of the breast (FELs) are a heterogeneous group of neoplasms exhibiting a histologic spectrum ranging from fibroadenomas (FAs) to malignant phyllodes tumors (PTs). Despite published histologic criteria for their classification, it is common for such lesions to exhibit overlapping features, leading to subjective interpretation and interobserver disagreements in histologic diagnosis. Therefore, there is a need for a more objective diagnostic modality to aid in the accurate classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Stroma tB in P2 shared signature genes with Stroma tC, including RGS5 , ITGA1 , NR2F2 , COL4A1/2 , THY1 , IGFBP7 , PDGFRB , NOTCH3 and ANGPT2 . A recent study demonstrated that the PI3K–Akt and MAPK pathways were upregulated in malignant breast PTs 32 ; here, our scRNA‐seq data showed that these pathways displayed heterogeneous enrichment in stromal cells (Figure S3 ).…”
Section: Resultssupporting
confidence: 57%
“…Stroma tB in P2 shared signature genes with Stroma tC, including RGS5 , ITGA1 , NR2F2 , COL4A1/2 , THY1 , IGFBP7 , PDGFRB , NOTCH3 and ANGPT2 . A recent study demonstrated that the PI3K–Akt and MAPK pathways were upregulated in malignant breast PTs 32 ; here, our scRNA‐seq data showed that these pathways displayed heterogeneous enrichment in stromal cells (Figure S3 ).…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, the PI3K‐AKT signaling pathway was investigated in both scRNA‐seq in PT tissues (Figure 3A ) and mRNA sequencing in cell lines (Figure 3C ). Previous reports suggested that activation of the AKT pathway may be associated with malignant transformation and recurrence of PT [ 18 , 19 ]. To confirm these sequencing results, the pathway was detected by WB, revealing that the PI3K‐AKT pathway was activated in malignant PT cells compared to benign PT cells (Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have identified CD146 as a marker of vascular endothelial cells. It has also been found that AA98 can inhibit angiogenesis [ 19 ]. Interestingly, in the AA98 application group, the size of 2 PDX tumors (from Donor 1 with lower level of CD146 compared to Donor 2 and 3) was larger than the size of 4 other PDX tumors (from Donor 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying specific genetic alterations associated with these lesions may provide additional tools for confirming their benign nature and distinguishing them from other breast conditions, including malignant tumors. This could enhance our ability to make precise diagnoses and guide appropriate clinical management [ 17 ].…”
Section: Reviewmentioning
confidence: 99%